Augmenting the productivity of double slope solar still by incorporating sensible and latent heat storage materials. Issue 1 (31st December 2023) - Agrawal, Rahul; Sharma, Tanmay; Gupta, Manish; Singh, Abhinandan; Upadhyay, Himanshu; Shrivastava, Ashish
ABSTRACT: The current experimental work aims to increase the productivity of solar desalination system by incorporating various types of heat storage materials namely pebbles, lauric acid and steel wool fibre to see its effect on yield. Therefore, two similar dimension double slope solar still were fabricated and compared in the similar environmental conditions of Bhopal, India (latitude 23.25°N and longitude 77.41° E). Hence, three different modified cases namely SSP (Still with pebbles as energy storage material), SSPCM (Still with lauric acid as PCM), SSSWF (Still with steel wool fibre) have been compared with CDSSS (conventional double slope solar still). The findings illustrates that the daily accumulative yield of CDSSS, SSP, SSPCM and SSSWF obtained was 1.325, 1.78, 2.255 and 1.865 kg/m 2 . The daily average energy efficiency values for CDSSS, SSP, SSPCM and SSSWF are found to be 16.6, 20.8, 23.81 and 21.03% respectively.